Terrors of the table : the curious history of nutrition - Gratzer, W. B. (Walter Bruno), 1932-2021 (Oxford University Press, 2005)
Tells the story of our struggle to recognise the connections between diet, health, and disease. This book combines the science of nutrition with a history of the fads and quackery that waylay the unwary when it comes to matters of food and health.